Factors Associated with the Incident of Diarrhea among Children - Putri, Nazwita Dewi; Novelia, Shinta; Ariesta, Erva Megia (KHD-Production, 2024)
Diarrhea is still a global problem with high levels of morbidity and mortality in various countries, especially in developing countries, and is one of the main causes of high rates of child morbidity and mortality in the world. The number of diarrhea sufferers found in Indonesia is estimated to be around 60 million cases every year. The number of diarrhea incidents in Dr. M. Yunus in Bengkulu Province in 2017 there were still 193 toddlers (13.3%). To determine the factors associated with the incidence of diarrhea in toddlers at RSUD Dr. M. Yunus Hospital Bengkulu Province in 2017. This research is an analytical survey with a cross sectional design. The sampling technique was carried out using a total sampling of 150 toddlers. The research instrument consisted of a questionnaire about socio-economic status and rotavirus immunization. Meanwhile, the questionnaire contains knowledge about the incidence of diarrhea. This questionnaire has been tested for validity and reliability with a Cronbach's alpha coefficient value of 0.752. Data were analyzed using univariate and bivariate analysis. From 150 samples, it was found that the largest group of respondents did not suffer from diarrhea, 113 respondents (75.3%), with 111 respondents (98.2%) having good knowledge, 81 respondents (98.8%) who had good socio-economic status. good nutritional status of 84 respondents (96.6%) and rotavirus immunization of 112 respondents (97.4%). The results of analysis using the chi-square test showed that there was a significant relationship between maternal knowledge (P= 0.000), socio-economic status (P= 0.000), nutritional status (P= 0.000), and rotavirus immunization (P= 0.000) with the incidence of diarrhea. in toddlers at RSUD Dr. M. Yunus Hospital Bengkulu Province 2017. There is a relationship between the incidence of diarrhea in toddlers at Dr. M. Yunus Hospital Bengkulu Province with maternal knowledge, socio-economic status, nutritional status, and rotavirus immunization. It is hoped that health workers can provide more education in the community to increase mothers' knowledge about diarrhea so that it can help prevent diarrhea incidents.